The Political Economy of Broadband Cost Recovery: South Korea, USA and EU - Roslyn Layton; Petrus Potgieter (International Telecommunications Society (ITS), 2023)
The United Nations in pursuit of global connectivity estimates a gap in broadband investment of 2 trillion and the stalling of internet adoption for lack of access and affordability. To ensure broadband access and affordability for end users, policymakers now explore broadband cost recovery, a rational, linear process to account for and attribute network traffic and cost to its source and the associated augmentation of financing to ensure the economic sustainability of broadband networks. The political economy of the evolving cost recovery approaches in South Korea, the United States, and the European Union are compared for philosophy, shortfall, goal, policy instrument, and legislation. The categories of recovery solutions (market-based, regulatory, or technological) are described with associated policy instruments (market-based negotiation, contributions to universal service etc.). Broadband Cost recovery is pursued for more than the nominal need to address market shortfalls, but for social goals such as affordability, fundamental rights, and the legitimacy of the state itself. As digitization and broadband-enabled technologies become increasingly integrated, the set of broadband regulatory policies is an important activity of government. Nations increasingly consider broadband cost recovery policy in light of their connectivity goals and attempt to optimize the business models of the digital economy to resolve shortfalls in broadband investment, adoption, and affordability. European regulatory policymaking is explored as something more than merely serving political interests but in delivering the larger goal of European Union legitimacy within the global sphere. European Union appears to increasingly call upon fundamental rights as justification for state intervention. This is contrasted with the US approach of pragmatism in technology policy, where the role of "rights" frequently vitiates regulation and state intervention. South Korea appears to maintain its approach of strengthening its long-standing framework to deliver global broadband technology leadership.
Keywords: 330